AB0642 Efficacy of anakinra in gouty arthritis in real life population: a report of 36 cases. (23rd January 2014) - Ottaviani, S.; Molto, A.; Ea, H.-K.; Neveu, S.; Gill, G.; Brunier, L.; Palazzo, E.; Meyer, O.; Richette, P.; Bardin, T.; Allanore, Y.; Lioté, F.; et al.
Abstract : Background: Gout is a common arthritis that occurs particularly in subjects who have frequently associated comorbidities. These comorbid conditions could limit the use of conventional therapies ( e.g. colchicine, non-steroidal anti-inflammatory drugs and/or corticosteroids). Objectives: The aim of the herein study was to evaluate the efficacy and tolerance of anakinra in patients with urate crystal-induced arthritis. Methods: We performed a multicentric retrospective chart review of patients who received anakinra for gouty arthritis. Demographic information, comorbidities, co-medication, treatment outcomes, adverse event and subsequent flares were recorded. The change of pain (VAS 0-100 mm) and CRP levels were evaluated at baseline and after 3 days of SC injections of anakinra (100 mg). The outcome of anakinra treatment was categorized as: good response (> 50% of improvement of VAS pain and CRP level), partial response (20 to 50% of improvement), or no response. Results: A total of 36 patients (29 males, mean age: 60.4 ± 13.4 years) who were treated by anakinra for gouty arthritis were included. The mean disease duration was 9.3 ± 9.0 years. All patients had contraindication and/or failure to at least two conventional therapies. The majority (33 [91.7%]) of patients demonstrated a good response to anakinra therapy. IL-1 blockade led to a strong and rapid decrease of VAS pain (72.5 [70.0-80.0] to 20.0 [20.0-30.0] mm, P <0.0001) and CRP level (130.5 [62.3-239.5] to 18.0 [5.0-29.5] mg/l, P <0.0001). After a median follow-up of 7.5 [2.0-12.3] months, a relapse occurred in 12 (33.3%) patients with a median delay to relapse of 22.5 [13.8-97.5] days. Relapse occurred more frequently in patients without prevention of acute flare ( P =0.014). None patient under anakinra for long-term use relapsed. Seven infections were noted and no case of neutropenia was observed. Conclusions: Our results confirm that anakinra is efficient in gouty arthritis, relatively well tolerated and could be a relevant alternative in the management of gouty arthritis, particularly in patients for whom conventional therapies are ineffective or contra-indicated. Disclosure of Interest: None Declared